(untitled) (Journal of the College of Education for Women, 2023)
The present work is qualitative descriptive. It aims to examine the idiosyncratic schema when deciphering the selected violence-based panel from Nasser Ibrahim’s caricatures. The researchers accordingly adopted part of Sharifian’s (2011) Cultural Schema model, particularly that part that is concerned with the examining the micro/idiosyncratic level of understanding. The study has revealed that the participants have not only differed among themselves regarding the way a figure is being denotatively conceptualized, they also highlighted different exact conceptualizations for the same figure, such as: using various adjectives that reflect various levels of intensity, emphasizing the behavioral aspect or the appearance of the figure, adopting different patterns of thinking like: metaphoric, metronomic, generic, specific, comprehensive or linear. Besides, based on their various points of attention and cognitive schema, they varied in conceptualizing the type of violence being depicted in this image as: psychological, verbal, physical, domestic violence or as the combination of more than one type. Finally, knowing about cultural schema does not involve to exemplify them in one’s behavior.